Fano Resonances: Tunable Fano Resonance and Plasmon–Exciton Coupling in Single Au Nanotriangles on Monolayer WS2 at Room Temperature (Adv. Mater. 22/2018). Issue 22 (May 2018) - Wang, Mingsong; Krasnok, Alex; Zhang, Tianyi; Scarabelli, Leonardo; Liu, He; Wu, Zilong; Liz‐Marzán, Luis M.; Terrones, Mauricio; Alù, Andrea; Zheng, Yuebing
Abstract : In article number1705779, Alex Krasnok, Andrea Alú, Yuebing Zheng, and co‐workers demonstrate tunable Fano resonances that arise from the interactions between the excitons of monolayer WS2 and the localized surface plasmon resonances of single Au nanotriangles (AuNTs) at room temperature. The resonance tuning is realized by varying the dielectric constants of the surrounding solvents or the dimensions of the AuNTs. A transition from weak to strong plasmon–exciton coupling is also observed by changing the dielectric constants of the surrounding solvents of the AuNTs.